Oceanic Aerosol Loading Derived From MISR's 4.4 km (V23) Aerosol Product. Issue 17 (10th September 2019) - Witek, Marcin L.; Garay, Michael J.; Diner, David J.; Smirnov, Alexander
Abstract: A new version (V23) of the Multi‐angle Imaging SpectroRadiometer (MISR) Level 2 (swath‐based) aerosol product was publicly released in mid‐2018. V23 has seen many updates to the retrieval process, most notably over dark water (DW), which applies over the global oceans and other deep bodies of water. Here the quality of the new MISR DW retrievals is assessed using surface‐based aerosol optical depth (AOD) observations from the Maritime Aerosol Network (MAN) and island/coastal sites within the AErosol RObotic NETwork (AERONET). About 406 MISR/MAN and 11, 015 MISR/AERONET collocated observations were identified. Comparison against MAN reveals the unparalleled accuracy of the V23 AOD retrievals: the correlation coefficient is 0.98, the root‐mean‐square error is 0.041, and the mean bias is −0.002. Aerosol spatial heterogeneity negatively affects comparison statistics against AERONET observations—applying stricter collocation criteria drastically improves agreement between MISR and AERONET. The reported AOD uncertainties realistically represent retrieval errors as they exhibit behavior similar to that of the standard deviation of a Gaussian distribution. Over the 18 years of MISR data analyzed, the global area‐weighted average AOD over oceans is 0.103; it becomes 0.151 when the averaging is restricted to locations where MAN observations are available. The AOD uncertainties are generally higher than average in offshore areas dominated by anthropogenic and biomass burning aerosols and lower than average in regions with mineral dust outflows. These results suggest future directions for improving the predefined aerosol mixtures used in the MISR aerosol retrieval look‐up tables. Key Points: New MISR Version 23 dark water AOD retrievals show excellent agreement with surface‐based observations Reported AOD pixel‐level uncertainties realistically represent retrieval errors Climatology of AOD and associated uncertainties over oceans are analyzed